Optimization of gabapentin dosage in pediatric patients with renal impairment: a physiologically based pharmacokinetic modeling approach - Qin, Xiaoli; Shen, Chaozhuang; Li, Zhimin; Yang, Yujie (Frontiers in Pharmacology, 2025)
BackgroundGabapentin (GAB) is an adjunctive antiepileptic drug widely used in pediatric patients. However, little is known about its pharmacokinetics in pediatric patients under 3 years old or with renal impairment (RI). To address this, we developed a physiologically based pharmacokinetic (PBPK) model for precise dosing guidance.MethodsA PBPK model for GAB was first developed in healthy adults using PK-Sim® and then extended to pediatric populations, accounting for age-related physiological changes. For RI simulations, reduced glomerular filtration and tubular secretion were incorporated based on adult RI models.ResultsThe PBPK model accurately predicted GAB exposure in adults and children after single and multiple administration (geometric mean fold error <2). Plasma concentrations and PK parameters were similar in children under 3 years old and those aged 3-12. In pediatric RI patients under 12 years old, AUC0- ∞ increased to 2.09-, 3.30-, and 31.67-fold for mild, moderate, and severe RI, respectively, compared to healthy children. Dosing frequency was adjusted to bid (mild RI), qd (moderate RI), and qod (severe RI), with an additional 50% dose reduction for severe RI.ConclusionPBPK models provide better guidance for GAB dosing in pediatric patients with varying RI degrees, laying a foundation for precision therapy. This study is a significant step in optimizing GAB treatment for this high-risk pediatric population.